Teaching communication skills: Getting things done (Requesting and responding) - Joshi, Rajendra (Journal of NELTA, 2018)
Making communication meaningful in English as a foreign language (EFL) context like Nepal is very essential. This lesson focuses on socializing, where students make requests and respond to the requests made.